THE ROLE OF SOCIETY IN EDUCATIONAL SCIENCE - Devi Sakinah Nasution; Firman; Riska Ahmad (Literasi Nusantara, 2021)
Education in society are two things that are interrelated. Education is always changing in developments that occur in society or community needs. Educational institutions are given the freedom to manage their institutions according to the needs of the surrounding community and involve community participation in carrying out their educational process. To realize this, of course, various fields in the organizational structure of school institutions are functioned optimally, not only those of an academic nature that are considered but also those that are supportive in this case the field of public relations which is a mediator of communication between educational institutions and the community. This is what educational institutions and the community have not realized where they still consider two separate parts so that there is no concern for each other's existence, even though they are two groups that cannot be separated in the implementation of the educational process to produce a moral generation of moral society.